2021
DOI: 10.18415/ijmmu.v8i7.2849
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health Promotion with WhatsApp Media and Booklets on Knowledge Level and Attitude about HIV/Aids

Abstract: The purpose of this study was to determine the effect of health promotion with social media and booklets on students' knowledge and attitudes about HIV/Aids. This research uses Quasi Experimental method with pretest-posttest control group design. The sampling technique used is random sampling, and analyzed by t-test with the Stata 13 program. The population in this study were students of Kusuma Husada University Surakarta batch 2019 of the Bachelor of Nursing Study Program. The sample in this study used random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…The results of this study are in line with the opinion of Haenlein in Adriana & Herdhianta (2021) who revealed that social media is defined as online media where users can easily participate, share, and create works or content (content). It can be concluded that WhatsApp media has an effect on increasing the knowledge of young women by about 1000 HPK.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study are in line with the opinion of Haenlein in Adriana & Herdhianta (2021) who revealed that social media is defined as online media where users can easily participate, share, and create works or content (content). It can be concluded that WhatsApp media has an effect on increasing the knowledge of young women by about 1000 HPK.…”
Section: Discussionsupporting
confidence: 89%
“…This booklet was designed and compiled by the researchers based on the information collected from scientific documents and needs assessment of female students and reproductive health service providers of Isfahan University of Medical Sciences. [ 16 ] This educational booklet has been written in 140 pages and 11 chapters including genital anatomy, vulvar and vaginal diseases, menstruation and related issues, polycystic ovarian syndrome, breast diseases, urinary tract infections, sexually transmitted diseases, AIDS and hepatitis, contraceptive methods, sexual harassment, and cervical cancer. The booklet includes information which can be used by every individual, without the need for a professional instructor, to help identify, prevent, and provide care for prevalent early reproductive health problems in young girls.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, an educational booklet that is used for health promotion has several advantages; it can lead to independent responsibility of each respondent for knowledge on the basis of information received through the booklet and can be studied at any time and anywhere. [ 16 ] Moreover, the needs assessment of students showed that the preferred method for participating in training plans was the nonattendance method, and among these methods, mobile software and educational booklet got the most scores. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Booklets are one of the media used in this study, booklets were chosen because booklets are often used for health education until now (Isnaningsih, 2019). Adriana et al (2021) wherever they go compared to other media such as booklets. In addition, the booklet has disadvantages, namely reading skills, and the process of delivering the message is not directly to the respondent so that it requires a simple and easy-to-understand word selection by the reader so that there is no misinterpretation by the reader (Wulandari, 2020).…”
Section: Overview Of Hiv/aids Prevention Behavior In Health Belief Mo...mentioning
confidence: 99%